Effect of Lighting on the Intensification of Phycocyanin Production in a Culture of Arthrospira platensis - Dawid Szwarc; Marcin Zieliński (Proceedings, 2018)
The global market shows high demand for products of natural origin to reduce the use of synthetic substances in the food, pharmaceutical and cosmetics industries. One of the opportunities for acquiring natural compounds of industrial value is the use of cyanobacteria biomass. In terms of biomass composition, cyanobacteria of the species Arthrospira platensis deserve particular attention. They are characterised by high contents of protein, γ-linolenic acid, polysaccharides, β-carotene, chlorophyll and phycocyanin. Phycocyanin is a pigment-protein complex widely used in the food and cosmetics industry. It is also used as fluorescent probes in histochemistry, fluorescence microscopy, flow cytometry and fluorescence immunoassay. Due to the extensive use of phycocyanin in various industries, a high demand for this pigment is generated, which determines the search for methods of intensifying phycocyanin production by the cells of A. platensis. The aim of the study was to determine the effect of light of different wavelengths on phycocyanin productivity by cyanobacteria of the species Arthrospira platensis. The highest biomass concentration and phycocyanin concentration were obtained in a culture using Red LED lighting.